Association of triglyceride glucose-body mass index (TyG-BMI) with metabolic dysfunction-associated steatotic liver disease: A systematic review and meta-analysis - Yasaman Ghodsi Boushehri; Zahra Meymanatabadi; Ali Ezzatollahi Tanha; Pouria Azami; Maryam Alaei; Amir Ali Alamdari; Hooman Momtazi; Nasrin Deilami Moezzi; Amirhossein Habibzadeh; Shaghayegh Khanmohammadi (PLoS ONE, 2025)
Background TyG-BMI has been proposed as a marker of insulin resistance in metabolic-associated fatty liver disease, but its clinical utility remains uncertain. This study aims to evaluate the association between TyG-BMI and metabolic dysfunction-associated steatotic liver disease (MASLD) through a systematic review and meta-analysis, focusing on the diagnostic performance across different subgroups. Methods A comprehensive literature search was conducted in PubMed, Scopus, Embase, and Web of Science up to January 20, 2025. Studies evaluating the relationship between TyG-BMI and MASLD in adults were included. A random-effects model was employed to pool effect sizes, and subgroup analyses were conducted based on sex, disease definition, and population type. Results Thirty-five studies with 339,087 participants were included. The pooled mean difference for TyG-BMI between MASLD and non-MASLD groups was 42.72 (95% CI: 35.93–49.51; p < 0.0001). Subgroup analysis revealed higher mean differences in the metabolic-associated fatty liver disease (MAFLD) group (49.56, 95% CI: 39.38–59.74) compared to non-alcoholic fatty liver disease ase (NAFLD) (34.68, 95% CI: 28.45–40.91). The odds ratio per one-unit increment of the TyG-BMI was 1.05 (95% CI: 1.03–1.08). Sensitivity for TyG-BMI in diagnosing MASLD was 0.79 (95% CI: 0.73–0.84), and specificity was 0.76 (95% CI: 0.71–0.80). The pooled area under the curve (AUC) for TyG-BMI was 0.83 (95% CI: 0.81–0.86), with better performance in females (0.88) compared to males (0.83). Subgroup analysis by disease definition showed a higher AUC for MAFLD (0.87) compared to NAFLD (0.81). Conclusion TyG-BMI is a promising diagnostic marker for MASLD, with higher diagnostic performance in MAFLD and among females. Further studies are needed to confirm these findings in diverse populations.